Fungsi Kepemimpinan dalam Meningkatkan Pelayanan Publik di Kantor Camat Rasanae Barat Kota Bima - Nofita Nofita (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This study aims to determine the Leadership Function in Improving Public Services at the West Rasanae Sub-District Office, Bima City. Because it is expected that the leadership function of the Camat can improve employee work services. This research refers to the indicators of Hadari Nawawi's leadership function (1992). This research was conducted at the West Rasanae Sub-District Office, Bima City. Camat Rasanae Barat and sub-district employees. Data collection techniques were carried out by observation, interviews, and documents and field notes. Then the data was analyzed descriptively qualitative. The results showed that the leadership function in improving public services can be said to be optimal, indicators: 1) consultative 2) participation 3). although public services are still categorized as not optimal, namely instructive indicators. However, the participatory function has been maximized. Judging from the participation of employees in the activities and work plans of the sub-district government, who are always active and consultative, the progress of human resources is still low so that they cannot plan properly for instructions from the sub-district head, such as there are still employees who lack mastery of technology and the ability to operate computers so that office work cannot be completed in a timely manner.